INCIDENCES OF CANDIDA ALBICANS AND NON-ALBICANS AMONG CATHETER-ASSOCIATED URINARY TRACT INFECTION PATIENTS OF AKOLA CITY - Ln, Khandare; Dl, Barate (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Candida spp. is the third leading cause of catheter-related infections. Candida species is a part of human microflora and it becomes pathogenic when certain conditions are present and cause an opportunistic infections. The present study was undertaken to determine incidences of Candida albicans and non-albicans among catheterized urinary tract infection (UTI) patients of Akola city. Methods: A total 60 catheter urine samples were collected from patient of all the age group and both sex who had indwelling urinary catheter. The collected catheterized urine samples of patients from various hospitals of Akola city were used for isolation using HiCrome Candida differential agar. Results: It was found that highest frequency of isolation of Candida spp. was from age group 61-70 years. The predominance of male candidate was more than female having Candida spp. in catheter-associated UTI (C-UTI). Among the Candida spp. C. albicans (64.81%) was predominant over non-albicans spp. while in non-albicans Candida krusei and Candida glabrata were predominant showing 11.11% incidences. It was followed by Candida tropicalis (9.2%) and Candida parapsilosis (3.7%). Conclusion: The incidences of C. albicans and non-albicans were high among catheter-associated UTI patients.